Revisão sistematizada sobre a utilização do plasma gel como biomaterial para harmonização orofacial - Oliveira, Ane Micheline Machado de (2021)
The objective of this systematized review was to evaluate the viability of plasma gel as a biomaterial in orofacial harmonization, analyzing studies related to methodology, structural analysis, results, effectiveness and the safety of this autologous concentrate in the form of thermally processed gel. Material and Methods: A comprehensive search was performed on MEDLINE via PubMed, LILACS, and BBO and Scholar Google. Results: A total of 9 studies were identified. The studies evaluated the various methodologies presented and the average follow-up time was 6 months. Even with different methodologies, most studies concluded that favorable reports in vitro tests and clinical therapies with plasma gel. Conclusion: The results of the studies included in this review suggest that plasma gel is a promising biomaterial for application in Orofacial Harmonization and the synergy between variations in platelet aggregates in the future will enable efficient methodological standardizations for the development of dermal regeneration. Further studies with standardized protocols, a larger sample size and follow-up time are needed to better define the efficacy, safety, and viability of this thermoprocessed blood plasma concentrate.